Accruing evidence on benefits of adherence to the Mediterranean diet on health: an updated systematic review and meta-analysis - Sofi, Francesco; Abbate, Rosanna; Gensini, Gian Franco; Casini, Alessandro (The American journal of clinical nutrition, 2010)
The Mediterranean diet has long been reported to be protective against the occurrence of several different health outcomes. We aimed to update our previous meta-analysis of published cohort prospective studies that investigated the effects of adherence to the Mediterranean diet on health status. We conducted a comprehensive literature search through electronic databases up to June 2010. The updated review process showed 7 prospective studies published in the past 2 y that were not included in the previous meta-analysis (1 study for overall mortality, 3 studies for cardiovascular incidence or mortality, 1 study for cancer incidence or mortality, and 2 studies for neurodegenerative diseases). These recent studies included 2 health outcomes not previously investigated (ie, mild cognitive impairment and stroke). The meta-analysis for all studies with a random-effects model that was conducted after the inclusion of these recent studies showed that a 2-point increase in adherence to the Mediterranean diet was associated with a significant reduction of overall mortality [relative risk (RR) = 0.92; 95% CI: 0.90, 0.94], cardiovascular incidence or mortality (RR = 0.90; 95% CI: 0.87, 0.93), cancer incidence or mortality (RR = 0.94; 95% CI: 0.92, 0.96), and neurodegenerative diseases (RR = 0.87; 95% CI: 0.81, 0.94). The meta-regression analysis showed that sample size was the most significant contributor to the model because it significantly influenced the estimate of the association for overall mortality. This updated meta-analysis confirms, in a larger number of subjects and studies, the significant and consistent protection provided by adherence to the Mediterranean diet in relation to the occurrence of major chronic degenerative diseases.